2021
DOI: 10.1186/s12873-020-00397-w
|View full text |Cite
|
Sign up to set email alerts
|

Health care providers’ perception of the frequent emergency department user issue and of targeted case management interventions: a cross-sectional national survey in Switzerland

Abstract: Background Frequent users of emergency departments (FUEDs) (≥5 ED visits/year) represent a vulnerable population with complex needs accounting for a significant number of emergency department (ED) consultations, thus contributing to EDs overcrowding. Research exploring ED staff perceptions of FUEDs is scarce. Objectives The current study aimed to evaluate in ED staff a) the extent to which FUEDs are perceived as an issue; b) their perceived levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…The larger survey included 19 closed and open-ended questions, in German, French, and Italian, (covering 99.2% of the Swiss population) assessing ED staff’s perception of FUED and interest in implementing CM. 16 Of those, the 2 questions exploring ED staff perceptions of challenges related to FUED care were used in the current study. Participants were asked to indicate the extent to which they perceive FUED to be problematic within their ED service, using a Likert scale ranging from 1 = a non-important problem to 4 = an extremely important problem .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger survey included 19 closed and open-ended questions, in German, French, and Italian, (covering 99.2% of the Swiss population) assessing ED staff’s perception of FUED and interest in implementing CM. 16 Of those, the 2 questions exploring ED staff perceptions of challenges related to FUED care were used in the current study. Participants were asked to indicate the extent to which they perceive FUED to be problematic within their ED service, using a Likert scale ranging from 1 = a non-important problem to 4 = an extremely important problem .…”
Section: Methodsmentioning
confidence: 99%
“…An online survey was sent to all general adult emergency services in Switzerland. 16 In total, 64% of participants perceived important challenges around FUED. Findings also indicated that the majority of ED staff face FUED regularly, yet they feel poorly informed on how to manage them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A 12-item online survey was developed to measure variables related to the FUED issue, summarized below and presented in Appendix 1. The survey was based on a version developed by a panel of experts involved with FUED and used in ongoing research [18,19]. As described in Chastonay et al [19], the panel conducted a series of sessions to develop a set of items exploring ED staff's perceptions regarding FUED and associated issues.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was based on a version developed by a panel of experts involved with FUED and used in ongoing research [18,19]. As described in Chastonay et al [19], the panel conducted a series of sessions to develop a set of items exploring ED staff's perceptions regarding FUED and associated issues. The survey was tested by ED staff (Lausanne university hospital, CHUV; N = 14).…”
Section: Methodsmentioning
confidence: 99%